Successful Endovascular Embolisation of an Unusual Giant Pseudoaneurysm of the Middle Colic Artery - Borzelli, Antonio; Cangiano, Gianluca; Silvestre, Mattia; Corvino, Fabio; Corvino, Antonio; de Magistris, Giuseppe; Niola, Raffaella (Journal of Endovascular Resuscitation and Trauma Management, 2022)
Visceral artery pseudoaneurysms (VAPAs) are extremely rare and pseudoaneurysms in the superior mesenteric artery (SMA) and its branches, particularly the middle colic artery, are the rarest. These account for 6–8% of all VAPAs with an incidence of 0.01%. They can be associated with an inflammatory disease (such as pancreatitis), infection or arise as a post-surgical complication, but they can also be due to a traumatic damage to the artery caused by a full-thickness slit in the arterial wall. They can be asymptomatic or manifest with symptoms such as abdominal pain, nausea and vomiting, local pressure symptoms (such as a pulsatile mass or a bruit) and gastrointestinal bleeding. Imaging techniques play a key role in the diagnosis of VAPAs and angiography still represents the gold standard, although nowadays it has a pivotal role for treatment with the possibility to perform an endovascular embolisation. In fact, although rare, VAPAs are of clinical importance mainly because they can cause life-threatening intra-abdominal or retroperitoneal haemorrhage and so prompt treatments are crucial, whether they are symptomatic, haemorrhagic or incidentally found. In the past, surgery was the treatment of choice, but in recent years with the improvement and development of interventional vascular techniques, surgery has been replaced by transcatheter endovascular embolisation due to its low morbidity and mortality and high success rate. In this article, we report the case of an unusual giant spontaneous pseudoaneurysm of the middle colic artery in a patient with a scoliotic abdominal aortic aneurysm successfully treated by endovascular embolisation.